2014
DOI: 10.5552/drind.2014.1340
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Mechanical Properties within Individual Annual Rings in the Resonance Spruce Wood (Picea abies (L.) Karst.)

Abstract: Variation in MechanicalProperties within Individual Annual Rings of the Resonance Spruce Wood ¢Picea abies (L.) Karst.£ Varijacije mehaničkih svojstava unutar pojedinih godova rezonantne smrekovineOriginal scientifi c paper • Izvorni znanstveni rad Received -prispjelo: 11. 7. 2013. Accepted -prihvaćeno: 23. 6. 2014 630*.811.4; 674.032.475.542 doi:10.5552/drind.2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Roszyk et al [29] reported that latewood modulus of elasticity (MOE) is higher than earlywood MOE for scots pine at low moisture content (8%). Similar results were obtained for Spruce wood [Picea abies (L.) Karst] [31] and loblolly pine [28][29][30][31][32] with an important increase in MOE values with the growth of annual rings. However, the preparation of initial and final wood samples was quite complicated and required perfectly parallel annual rings.…”
Section: Practical Implicationssupporting
confidence: 75%
See 1 more Smart Citation
“…Roszyk et al [29] reported that latewood modulus of elasticity (MOE) is higher than earlywood MOE for scots pine at low moisture content (8%). Similar results were obtained for Spruce wood [Picea abies (L.) Karst] [31] and loblolly pine [28][29][30][31][32] with an important increase in MOE values with the growth of annual rings. However, the preparation of initial and final wood samples was quite complicated and required perfectly parallel annual rings.…”
Section: Practical Implicationssupporting
confidence: 75%
“…This method was used to determine earlywood and latewood properties in order to obtain a more detailed characterization of wood mechanical behavior. Only a few studies have investigated earlywood and latewood elastic properties [28][29][30][31][32]. Roszyk et al [29] reported that latewood modulus of elasticity (MOE) is higher than earlywood MOE for scots pine at low moisture content (8%).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As a result, resonance wood is characterized by a small average MFA of 10 or less. Moreover, research has showed that a small difference between the average MFA of latewood compared to earlywood is beneficial for the acoustic properties, as this leads to a more homogeneous sound velocity ( [11,12]). A certain degree of continuity of this quantity over the violin plate is therefore desired.…”
Section: Wood Variabilitymentioning
confidence: 99%
“…Fact is that Norway spruce (Picea abiens) has a very small average MFA with respect to other wood species, to which it largely owes its preferred use in violin building. The MFA is known to decrease with the age of the growth ring, and also with tree height [11]. The decrease rate is however subject to uncertainty.…”
Section: Spatial Variabilitymentioning
confidence: 99%
See 1 more Smart Citation